An efficient approach to homochiral indane nucleosides - Ugliarolo, Esteban Ariel (2009)
A series of new chiral 6-substituted purinyl and 8-aza-purinyl carbonucleosides based on indanol were synthesized from the commercially available (1R,2S)-1-amino-2-indanol and (1S,2R)-1-amino-2-indanol based on a well-known methodology.